Sleep quality and low-density lipoprotein cholesterol levels with the risk of ischemic stroke - Sari, Nur Amalia; Sulistyani, Sulistyani; Rosyidah, Devi Usdiana; Romadhon, Yusuf Alam (JHeS (Journal of Health Studies), 2025)
Stroke is a multi-causal disease, and many factors can lead to stroke. There are also some unseen behavioral factors, such as poor diet. In recent years, poor sleep quality has been considered a potential trigger of stroke. If these factors are not well controlled, it can have an impact on the incidence of ischemic stroke. The aim of this research is to assess the correlation between sleep quality and low-density lipoprotein cholesterol levels with the incidence of ischemic stroke. This study used an analytic observational design with a cross-sectional approach using the PSQI (Pittsburgh Sleep Quality Index) questionnaire and secondary data. A total of 60 respondents were selected with a purposive sampling technique and met the inclusion and exclusion criteria. This research was conducted at Fatmawati Soekarno Hospital, Surakarta City. Statistical analysis showed that the Chi-Square test produced a significance value, with a p value of 0.007 for the correlation of sleep quality with the incidence of ischemic stroke, and a p value of 0.688 for the correlation of low-density lipoprotein cholesterol levels with the incidence of ischemic stroke. It can be concluded that there is a correlation between sleep quality and the incidence of ischemic stroke, but there is no relationship between low-density lipoprotein cholesterol levels and the incidence of ischemic stroke.